PENGARUH MOTIVASI, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. PERTAMINA RU VI BALONGAN - Melyna Putri Wijayasari; Wahyu Hidayat; Saryadi Saryadi (Universitas Diponegoro, 2013)
The research was conducted to determine the influence of motivation, discipline of work and job satisfaction for the employee’s performance in the production PT Pertamina RU VI Balongan. This type of research is explanatory with the techniques of data collection through questionnaire. The sampling technique used sampling saturation, the sample of 70 peoples who are the employee of production PT Pertamina RU VI Balongan. The method of analysis used in this study is Quantitative data analysis, the method of data analysis used simple linear regression analysis and multiple linear regression. Based on the results of the research it can be conclude that : a) motivation has positive and significant impact on employee performance 53,6%;(b) discipline of work has positive and significant impact on employee performance 61,4%; (c) job satisfactionhas positive and significant impact on employee performance 47,7%; (d)variable effect of motivation (X1), discipline of work (X2), and job satisfaction (X3) value significant positive effect on employee performance (Y)in the amount of 73,7%. The advice can be given to improve the performance of the employees of the production company PT Pertamina RU VI Balongan is to keep and maintain a conducive situation in the company such as corporate governance and increase professionalism in the work.